Shared heritability and functional enrichment across six solid cancers - Jiang, Xia; Brenner, Hermann; Burwinkel, Barbara; Chang-Claude, Jenny; Hamann, Ute; Hoffmeister, Michael; Risch, Angela (Nature Communications, 2019)
Similarities in cancers can be studied to interrogate their etiology. Here, the authors use genome-wide association study summary statistics from six cancer types based on 296,215 cases and 301,319 controls of European ancestry, showing that solid tumours arising from different tissues share a degree of common germline genetic basis.